PEMETAAN KERAWANAN BANJIR DI KOTA SURAKARTA - Ramadhan, Faisal Adyaksa; Hadiani, Rintis; Muttaqien, Adi Yusuf (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
Floods have become one of the problems occurring in the city of Surakarta. The floods are caused by the overflow of the tributaries of the Bengawan Solo River, located within the Surakarta City area. One of the strategies for flood disaster management is through flood zone mapping. In flood vulnerability mapping, hydrological analysis is conducted to determine the magnitude of the flood discharge for different return periods (Q2, Q5, Q10, Q25, and Q50) using the HSS SCS method, which will serve as input for the HEC-RAS program to simulate floods, used as determining variables in flood vulnerability mapping. The results of the flood simulation analysis indicate that the level of vulnerability in non-vulnerable areas has a flood area limit ranging from 1.05 ha to 8.93 ha, a maximum flood depth limit ranging from 0.24 m to 0.57 m, and a maximum flood velocity limit ranging from 0.06 m/sec to 0.21 m/sec. For areas with low vulnerability, the flood area limit ranges from 8.93 ha to 16.80 ha, the maximum flood depth limit ranges from 0.57 m to 0.90 m, and the maximum flood velocity limit ranges from 0.21 m/sec to 0.35 m/sec. For areas with moderate vulnerability, the flood area limit ranges from 16.80 ha to 24.68 ha, the maximum flood depth limit ranges from 0.90 m to 1.23 m, and the maximum flood velocity limit ranges from 0.35 m/sec to 0.50 m/sec. For areas with high vulnerability, the flood area limit ranges from 24.68 ha to 32.55 ha, the maximum flood depth limit ranges from 1.23 m to 1.55 m, and the maximum flood velocity limit ranges from 0.50 m/sec to 0.64 m/sec.